Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Diskusi Terhadap Kepercayaan Diri Santri Panti Asuhan Abadi Aisyiyah Parepare - Jufri Jufri (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to examine the effect of group guidance services using discussion techniques on the self-confidence of students at the Abadi Aisyiyah Orphanage in Parepare. Self-confidence is an essential aspect of individual development, especially for students living in orphanages who often experience limited social support. This research employed a quantitative approach with a survey method. The sample consisted of 30 students selected randomly. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using simple linear regression. The results showed that group guidance services using discussion techniques had a positive and significant effect on students' self-confidence. This is indicated by the t-value of 6.121 with a significance level of 0.000 < 0.05. The regression equation obtained was Ŷ = –13.080 + 0.909X, with a coefficient of determination (R²) of 0.572. This means that 57.2% of students' self-confidence is influenced by group guidance services using discussion techniques. Based on these findings, it can be concluded that group guidance services using discussion techniques are effective in improving students' self-confidence. Therefore, this service is recommended to be implemented continuously in orphanage development programs.